Spinal pain and nutrition in adolescents - an exploratory cross-sectional study - Oddy Wendy H; Straker Leon M; Perry Mark C; O'Sullivan Peter B; Smith Anne J (BMC Musculoskeletal Disorders, 2010)
Abstract Background Spinal pain is an important health issue for adolescents resulting in functional limitations for many and increasing the risk of spinal pain in adulthood. Whilst human and animal studies suggest nutrition could influence spinal pain, this has not been investigated in adolescents. The objective of this exploratory cross sectional study was to evaluate associations between diet and adolescent spinal pain. Methods This study surveyed the spinal pain (neck and back) and nutrition (specific nutrients, broad food groups, diet quality and dietary pattern) of 1424 male and female adolescents at 14 years of age, in Western Australia. Results Back or neck pain were experienced by around half of the adolescents, with females more likely to experience spinal pain. Nutrition differed between sexes and deviated from optimal intakes. Vitamin B12, eggs, cereals and meat consumption were related to spinal pain in sex specific multivariate analyses including primary carer education level and adolescent waist girth and smoking. Conclusions The findings of this study suggest that certain aspects of diet may have an association with spinal pain in adolescence.